2013
DOI: 10.1016/j.msea.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of nickel processed by accumulative roll bonding

Abstract: A detailed investigation of the microstructure and mechanical properties has been conducted in pure nickel deformed to high strains using accumulative roll bonding (ARB). Samples have been investigated after different numbers of ARB cycles and the results have been compared with data for nickel processed by other deformation techniques, with particular focus on conventional rolling. It is found that the structural evolution in ARB-processed nickel is rapid at low strains followed by a slower evolution as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 40 publications
6
28
0
1
Order By: Relevance
“…Similar to the observations of heavily deformed materials produced by other deformation techniques [3][4][5][6], it has been found that the average boundary spacing in ARB-processed materials decreases with increasing strain, whereas the fraction of high angle boundaries (HABs) increases [7][8][9][10].…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similar to the observations of heavily deformed materials produced by other deformation techniques [3][4][5][6], it has been found that the average boundary spacing in ARB-processed materials decreases with increasing strain, whereas the fraction of high angle boundaries (HABs) increases [7][8][9][10].…”
Section: Introductionsupporting
confidence: 75%
“…The observed variations in both texture and the heterogeneity in microstructural refinement highlight the fact that even though the average boundary spacing approaches a saturation value with increasing number of ARB cycles [10], the microstructure and texture experience significant changes as each successive surface layer is moved to the center and then deformed under PSC conditions.…”
Section: Texture Gradientsmentioning
confidence: 95%
See 1 more Smart Citation
“…The higher strength in the DPD-processed PM2000 is consistent with the finer microstructure in this material. The increase in strength of PM2000 during DPD is accompanied by a significant reduction in ductility-a phenomenon which has previously been observed in many cold-deformed materials due to their limited capacity of work hardening [8,27,28].…”
Section: Nanostructure and Strengthmentioning
confidence: 62%
“…It has been shown that ARB to high strains results in significant structural refinement and large fractions of high angle boundaries (HABs). For example, the average boundary spacing measured along the normal direction (ND) in ARB-processed nickel after a von Mises strain ε vM of 6.4 is ~0.1 µm and the fraction of HABs is ~60 % [3]. There are, however, significant through-thickness heterogeneities both in texture [4][5][6][7][8][9][10] and in the deformed microstructure [9][10][11][12][13][14] after ARB.…”
Section: Introductionmentioning
confidence: 99%